2018
DOI: 10.1590/s1517-707620180004.0561
|View full text |Cite
|
Sign up to set email alerts
|

Tooth whitening affects bond strength of adhesive systems in enamel

Abstract: This study presents how the tooth whitening affects the bond strength and fracture type of three distinct adhesivesa conventional, a self-etching, and a universal adhesivein enamel. Health bovine incisors were prepared by flattening the labial surface; part of these teeth was submitted to whitening treatment with a peroxide-based product (WhiteGold Office © 35%). The Single Bond © , AdheSE © , or Single Bond Universal © adhesive system were used to adhere a block of restorative resin to the flat surface of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Regarding the properties related to enamel adhesion strength, fracture, and abrasion resistance after tooth bleaching, it was found that there are few studies on this reference, which generates insufficient data to reach concrete and reliable conclusions (Klarić et al, 2013;Lima Neto et al, 2018). The action of hydrogen peroxide present in Groups 2 and 3 would be physically altering the dental structure, leaving the enamel more porous and susceptible to pigmentation, to the detriment of an effective whitening action.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the properties related to enamel adhesion strength, fracture, and abrasion resistance after tooth bleaching, it was found that there are few studies on this reference, which generates insufficient data to reach concrete and reliable conclusions (Klarić et al, 2013;Lima Neto et al, 2018). The action of hydrogen peroxide present in Groups 2 and 3 would be physically altering the dental structure, leaving the enamel more porous and susceptible to pigmentation, to the detriment of an effective whitening action.…”
Section: Discussionmentioning
confidence: 99%